Pengaruh Membatik Jumputan (Tie Dye) Sebagai Terapi Seni untuk Mengurangi Tingkat Ansietas Bagi Lansia - Ayuningjati, Krisma Giri; Kartinah, Kartinah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to investigate the impact of art activities, especially tie-dye, on the reduction of anxiety levels among elderly residents in Wisma Andong Sumawi social care facilities. This study involved 9 elderly participants and collected data through interviews, observations, and documentation. This research method includes validity, reliability, normality, homogeneity, and hypothesis testing. The results of the study show that positive involvement in creative activities improves mental well-being. The conclusions of this study highlight the importance of a supportive environment in managing anxiety, which can adversely affect the health of the elderly due to various life challenges. Keywords : Tie Dye, Enderly and Anxiety.